Las disfunciones familiares un factor para el rendimiento académico, de los niños de Educación General Básica Elemental de la escuela de educación básica Jesús Infante de la ciudad de Riobamba, periodo académico 2023-2024. - Buñay Tenezaca, Yadira Marily (2024)
This research aimed to analyze how family dysfunction affects the academic performance of children attending "Jesús Infante" School of Basic Education during the 2023-2024 school year. A mixed research approach and a non-experimental design were applied, utilizing observation and survey techniques. The instruments used were an observation form and a questionnaire administered to 29 students and 29 parents to gather preliminary results.It was found that 4th-grade students experienced academic performance issues due to the challenges stemming from dysfunctional family dynamics. Forty-five percent of them live with only one parent, 10% live with their grandparents, and 45% live in nuclear families. In conclusion, students living with only one parent tend to experience low self- esteem, communication barriers, lack of affection, understanding, and respect. Twenty- one children achieved their required learning, while five children were close to achieving it; however, in conflict-ridden environments, students lose interest in learning. Such students exhibit shyness, distraction, and isolation, leading to learning difficulties.